2007
DOI: 10.1093/icb/icm030
|View full text |Cite
|
Sign up to set email alerts
|

Sexual segregation in vertebrates: proximate and ultimate causes

Abstract: Sexual segregation is very common in vertebrates that live in groups. In this article, I will review proximate and ultimate causes of sexual segregation in social species and in particular in ungulates in which the bulk of research on the topic has been carried out. In most social ungulate species, males and females live in separate groups outside the breeding season, sometimes using different home ranges and types of habitat. In most of these species, males are larger than females. Dimorphism in body size can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
129
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(139 citation statements)
references
References 63 publications
3
129
2
5
Order By: Relevance
“…Traditionally, sexual segregation in other vertebrates has been explained by predation risk, forage selection, or activity budgets (Ruckstuhl 2007). Predation risk does not explain occurrence in Disko Bay, as there are only few reports of killer whales in this area in winter and spring when bowhead whales are present in the bay, and no other predators (aside from humans) threaten bowhead calves in West Greenland.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, sexual segregation in other vertebrates has been explained by predation risk, forage selection, or activity budgets (Ruckstuhl 2007). Predation risk does not explain occurrence in Disko Bay, as there are only few reports of killer whales in this area in winter and spring when bowhead whales are present in the bay, and no other predators (aside from humans) threaten bowhead calves in West Greenland.…”
Section: Resultsmentioning
confidence: 99%
“…Association preferences between reproductive females could lead to a reduction of predation risk (Hamilton, 1971) for example, the presence of several kids in the same group may create a dilution effect that reduces the probability for a given kid to be preyed upon. Lactating females could also choose particularly safe habitats (Ruckstuhl, 2007), which could lead to segregation between lactating and nonlactating females (Barten et al, 2001). Lactating mountain goats stay approximately 20 m closer to escape terrain on average than nonlactating females in June when kids are vulnerable (Hamel & CĂŽte, 2007), but this distance was not large enough for lactating females to form separate groups.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in body size between sexes could create differences in time budgets, which may in turn affect the synchronization of individuals and prevent them from forming cohesive groups (Ruckstuhl, 1998(Ruckstuhl, , 1999. Differences in body mass and size can also explain why individuals sometimes segregate by age (Ruckstuhl, 2007). Croft et al (2005) showed that guppies, Poecilia reticulata, interacted more with individuals of similar body length than with other individuals.…”
mentioning
confidence: 99%
“…Lemur catta It is often expected that individuals within a population of different ages, sexes, and sizes, will exploit varying aspects of the species' feeding niche (Schoener 1986; Ebenman 1988). As part of this variation, sex differences in vertebrate feeding can range from temporal and spatial separation of males and females (Ruckstuhl and Neuhaus 2002;Ruckstuhl 2007) to differences in the composition and diversity in diet (CluttonBrock 1977a;Holmes 1986;Clarke et al 1998;Lewis et al 2002;Beck et al 2005;KrĂŒger 2005). For most species, however, little is known about when sex differences appear, how they change throughout development, if early sex differences mimic adult patterns, and if these sex differences function to partition resources or are only apparent with physiological differences between males and females, particularly those related to reproduction.…”
mentioning
confidence: 99%
“…Sex differences in feeding can be a result of sexdependent physiological costs, competition, and social dynamics (Clutton-Brock 1977a;Ruckstuhl 2007), and the developmental timing of the type and intensity of sex differences in feeding can help identify underlying causation. Sex differences in adult feeding are commonly linked to fluctuations in energetic and nutritional needs associated with sexual size dimorphism and costs of reproduction to females.…”
mentioning
confidence: 99%